Human occupations at the Alpysbaev Cave (western Tian Shan): Bioarchaeological insights from the Iron Age burial cluster - Abay Namen; Saine C. Hernandez Burgos; Aristeidis Varis; Emily Coco; Rachel Kalisher; Emily Gaul; Guido Alberto Gnecchi-Ruscone; Maria A. Spyrou; Cosimo Posth; Susanne Lindauer; David Naumann; Scott A. Williams; et al. (PLoS ONE, 2025)
For millennia, southern Kazakhstan has been at the center of population movements and cultural exchange, hosting numerous tribal unions and confederations. The social structures of the societies that formed these early states have been the subject of extensive research, interpreted primarily from burial structures and funerary rites. In a landscape dominated by kurgans, catacombs, and necropoles, little is known about the disposal of the dead in natural shelters like caves. In this paper, we present the initial results from the newly excavated site of Alpysbaev Cave located in Turkestan Province, southern Kazakhstan. Test excavations yielded several intersecting pits which contained disturbed adult and nonadult human remains (MNI = 4) as well as ceramic sherds, lithics, and by-products of combustion features. We radiocarbon dated material from our five lithostratigraphic units, which come from at least three distinct use phases spanning the Neolithic to early medieval and Iron Age periods. While the earliest lithostratigraphic unit contained human cranial fragments and faunal remains, most skeletal remains come from the Iron Age. We then present an integrated bioarchaeological and genetic evaluation of these remains and show evidence for subsistence practices, physical labour and pathological lesions among our sample.